The Effect of miR-10b Mimic Transfection on Invasion and Proliferation Gene Expression as the Direct Target of the miR-10b Pathway in T47D Breast Cancer Cell Lines - Dessy Arisanty; Zolkapli Eshak; Fatma Sri Wahyuni; Afifatul Achyar; Salsabila Putri Khairani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Breast cancer remains one of the leading causes of death in women worldwide, with high incidence and mortality rates. The abnormal expression of the small non-coding RNA, microRNA-10b (miR-10b), has been associated with breast cancer progression. miR-10b is involved in various biological processes, including proliferation, metastasis, and drug resistance. However, the underlying mechanism by which miR-10b contributes to breast cancer progression remains unclear. This study aimed to investigate the effect of miR-10b on the expression of HOXD10 and PI3K genes, as well as its impact on cell viability and proliferation in breast cancer cells. In this study, T47D breast cancer cells were transfected with mimic miR-10b using the FANA-oligo transfection method at concentrations of 1, 2.5, and 5 µM. Cell viability was assessed using the MTT assay, while HOXD10 and PI3K gene expression levels were measured using RT-qPCR and ELISA. Data were analysed using paired t-tests with SPSS, and results were considered statistically significant at p < 0.05. The results showed that mimic miR-10b induced a dose-dependent increase in cell proliferation. Notably, only HOXD10 gene expression was significantly affected by the transfection, while PI3K gene expression remained unchanged. Cells transfected with 5 µM miR-10b mimic exhibited the highest proliferation rate compared to non-transfected controls (p < 0.05). In conclusion, miR-10b promotes breast cancer cell proliferation by downregulating HOXD10 expression, independent of PI3K, suggesting it is a potential target for further investigation.